Correlating clinical and laboratory diagnostic modalities in the diagnosis of epidermolysis bullosa in a resource‐poor setting. (15th February 2022) - Mahajan, Rahul; Manjunath, Seema; Madakshira, Manoj Gopal; Chatterjee, Debajyoti; Bishnoi, Anuradha; De, Dipankar; Handa, Sanjeev; Dass Radotra, Bishan; Jamwal, Manu; Das, Reena
Abstract: Background: Mutational analysis and immunofluorescence antigen mapping (IFM) are recommended as the laboratory tools of choice for diagnosing EB. In the past, transmission electron microscopy (TEM) was considered the gold standard, and more recently, clinical diagnostic matrix (CDM) has shown good concordance with next‐generation sequencing (NGS). Methods: In this prospective diagnostic study, a skin biopsy was taken for TEM and IFM in consecutive patients with EB (aged >6 months) diagnosed clinically with CDM. Wherever possible, mutational analysis was done using targeted NGS. Results: Of the 80 patients diagnosed with CDM, skin biopsy specimens of 42 patients were assessed using TEM, and of 59 patients using IFM. NGS was done in 39 patients. Taking NGS as the gold standard for diagnosing EB (n = 39 patients), the concordance with CDM, TEM, and IFM were estimated at 84.6% (33/39), 78.5% (11/14), and 76% (19/25) respectively. CDM showed a substantial agreement with NGS ( k = 0.69, p < 0.001). Conclusions: In comparison to NGS, the highest concordance was seen with CDM followed by TEM and IFM in diagnosing major subtypes of EB.